Situation Report: Romania, 22 July 1976 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Program to Improve the Supply of Consumer Goods Presidential Decree on Pardon for Certain Offenders Soviet-Romanian Commission for Economic Co-Operation Yugoslav Defense Minister Visits Romania Romania's Reaction to Air France Hijacking and the Entebbe Raid